IDENTIFICATION OF Anisakis simplex IN PURPLE SPOTTED BIG EYE FISH (Priacanthus sp.) FROM SOUTH BALI WATER AREA - Amayliana Ajeng Nastiti; Sri Subekti; Kismiyati Kismiyati; Endang Wulandari Suryaningtyas (Jurnal Perikanan Unram, 2024)
Anisakis simplex infection in fishery products can be dangerous because it has zoonotic can transmitted infection from fish to humans. Purple spotted big eye fish (Priacanthus sp.) is one of the reef fish species produced in the waters of South Bali and is not immune to the zoonotic threat Anisakis simplex poses. This study was conducted to identify Anisakis simplex which is known to infect Purple Spotted Big Eye Fish (Priacanthus sp.) in the South Bali Water Area. The parameters observed in this study were related to the prevalence and intensity of Anisakis simplex in Purple Spotted Big Eye Fish (Priacanthus sp.). The research method used was descriptive quantitative with purposive sampling of fish samples. The samples used were 30 fish obtained from 15-20% of the catch of purple spotted big eye fish in the South Bali Water Area. The results of the study showed that the morphological identification that had been carried out showed that Anisakis simplex found to infect Purple Spotted Big Eye Fish (Priacanthus sp.) was an Anisakis simplex type III larva with a prevalence rate of 26.3% classified as a frequent infection. The intensity value of Anisakis simplex in this study was 4.92 ind/fish and was classified as a low category. The predilection from this study showed that the most infections were in the intestinal organs.